High-temperature superconductivity on the verge of a structural instability in lanthanum superhydride - Dan Sun (Nature Portfolio, 2021)
The experimental studies to understand the superconductivity of superhydrides remain scarce. Here, the authors report pressure and magnetic field dependence of superconductivity in LaH10, and indicate lattice vibrations strongly affect superconducting coupling.